Persepsi Penggunaan Media Pembelajaran Berbasis Online Mahasiswa Pendidikan Geografi Universitas Negeri Semarang Menjelang Pandemi Covid-19 - Wijayanto, Pradika Adi; Nafi’ah, Khoirima; Pratomo, Vitho (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2021)
The Covid-19 pandemic has changed the pattern of the world of education. Changes are experienced by the learning system, from offline to online using online media. The research objectives are (1) to describe the types of online learning media used in Geography Education student lectures, (2) to analyze the advantages and disadvantages of online media based on perceptions, (3) to formulate strategies to make effective use of favorite online media based on student perceptions. The research method is a survey of qualitative descriptive data analysis techniques from filling closed and open questionnaires using purposive samples. The questionnaire was filled out by Geography Education students for even semesters (semesters 2-6) of UNNES in 2020 and then described. Based on the results of the study, it can be concluded that (1) the online media used are WhatsApp Group, Facebook Group, Facebook Live, Website, Zoom , Skype, Discord, Youtube Live, Instagram Live, Google Classroom, Quiz, Telegram Group, Elena, Hangout (2) The students' favorite online learning media are Discord, WhatsApp Group, Zoom , Elena, Google Classroom and Instagram live, and 3) strategies to make effective use of online learning media are 1) complementing other potential online media and can cover their weaknesses, 2) review and an analysis of whether the selected online media can be implemented using a learning method or model according to the plan. 3) collect data and analyze the dominance of student learning styles as the basis for determining the selection of online learning media.